Understanding lasers an entry-level guide - Hecht, Jeff (IEEE Press, 1994)
Written for students, managers, non-specialist engineers, and anyone who wants an accessible introduction to laser technology, this book provides practical, intuitive descriptions of the workings of major types of lasers and their applications.